Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Para resolver la expresión [tex]\(\sqrt{(x+5)(5-x)+(x+3)(x-3)}\)[/tex] y evaluarla en [tex]\(x = 0\)[/tex], sigamos los siguientes pasos:
1. Expandir cada término dentro de la raíz:
Primero, expandimos [tex]\((x+5)(5-x)\)[/tex]:
[tex]\[ (x+5)(5-x) = x \cdot 5 + x \cdot (-x) + 5 \cdot 5 + 5 \cdot (-x) = 5x - x^2 + 25 - 5x = -x^2 + 25 \][/tex]
Luego, expandimos [tex]\((x+3)(x-3)\)[/tex]:
[tex]\[ (x+3)(x-3) = x \cdot x + x \cdot (-3) + 3 \cdot x + 3 \cdot (-3) = x^2 - 3x + 3x - 9 = x^2 - 9 \][/tex]
2. Sumar las expresiones expandidas:
Sumamos [tex]\(-x^2 + 25\)[/tex] y [tex]\(x^2 - 9\)[/tex]:
[tex]\[ (-x^2 + 25) + (x^2 - 9) = -x^2 + x^2 + 25 - 9 = 16 \][/tex]
Observamos que las [tex]\(x^2\)[/tex] se cancelan, y solo nos quedamos con una constante:
[tex]\[ -x^2 + x^2 + 16 = 16 \][/tex]
3. Simplificar la raíz cuadrada:
La expresión dentro de la raíz cuadrada ya es una constante:
[tex]\[ \sqrt{16} \][/tex]
4. Calcular la raíz cuadrada de 16:
Sabemos que:
[tex]\[ \sqrt{16} = 4 \][/tex]
Por lo tanto, al evaluar la expresión original, obtendremos:
[tex]\[ \sqrt{(x+5)(5-x)+(x+3)(x-3)} = 4 \][/tex]
La respuesta correcta es:
[tex]\[ \boxed{4} \][/tex]
1. Expandir cada término dentro de la raíz:
Primero, expandimos [tex]\((x+5)(5-x)\)[/tex]:
[tex]\[ (x+5)(5-x) = x \cdot 5 + x \cdot (-x) + 5 \cdot 5 + 5 \cdot (-x) = 5x - x^2 + 25 - 5x = -x^2 + 25 \][/tex]
Luego, expandimos [tex]\((x+3)(x-3)\)[/tex]:
[tex]\[ (x+3)(x-3) = x \cdot x + x \cdot (-3) + 3 \cdot x + 3 \cdot (-3) = x^2 - 3x + 3x - 9 = x^2 - 9 \][/tex]
2. Sumar las expresiones expandidas:
Sumamos [tex]\(-x^2 + 25\)[/tex] y [tex]\(x^2 - 9\)[/tex]:
[tex]\[ (-x^2 + 25) + (x^2 - 9) = -x^2 + x^2 + 25 - 9 = 16 \][/tex]
Observamos que las [tex]\(x^2\)[/tex] se cancelan, y solo nos quedamos con una constante:
[tex]\[ -x^2 + x^2 + 16 = 16 \][/tex]
3. Simplificar la raíz cuadrada:
La expresión dentro de la raíz cuadrada ya es una constante:
[tex]\[ \sqrt{16} \][/tex]
4. Calcular la raíz cuadrada de 16:
Sabemos que:
[tex]\[ \sqrt{16} = 4 \][/tex]
Por lo tanto, al evaluar la expresión original, obtendremos:
[tex]\[ \sqrt{(x+5)(5-x)+(x+3)(x-3)} = 4 \][/tex]
La respuesta correcta es:
[tex]\[ \boxed{4} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.